2013
DOI: 10.1371/journal.pone.0082693
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence Imaging-Based High-Throughput Screening of Fast- and Slow-Cycling LOV Proteins

Abstract: Light-oxygen-voltage (LOV) domains function as blue light-inducible molecular switches. The photosensory LOV domains derived from plants and fungi have provided an indispensable tool for optogenetics. Here we develop a high-throughput screening system to efficiently improve switch-off kinetics of LOV domains. The present system is based on fluorescence imaging of thermal reversion of a flavin cofactor bound to LOV domains. We conducted multi site-directed random mutagenesis of seven amino acid residues surroun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
84
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(88 citation statements)
references
References 26 publications
4
84
0
Order By: Relevance
“…4). Residue substitutions at this site are known to have large effects on LOV kinetics in VVD and other proteins (18,36). Specifically, an I74V variant of VVD accelerates the photocycle 24-fold; however, it has no effect on solvent accessibility (18).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4). Residue substitutions at this site are known to have large effects on LOV kinetics in VVD and other proteins (18,36). Specifically, an I74V variant of VVD accelerates the photocycle 24-fold; however, it has no effect on solvent accessibility (18).…”
Section: Resultsmentioning
confidence: 99%
“…Position 101 has been implicated in tuning LOV domain kinetics in numerous systems, but its role in activating water has not been explored (18,31,36,46). Similarly, its effect on signaling mechanisms is not well known.…”
Section: Discussionmentioning
confidence: 99%
“…The slow photoswitches could be used to avoid some unwanted side effects caused by continuous irradiation, such as phototoxicity and unfocused activation owing to sample drift. Recently, methods to improve switch-off kinetics of blue light photoreceptors have been developed using bacterial or yeast colonies-based high throughput screening systems 28,29 . These screening methods can help to further accelerate or decelerate the switch-off kinetics of the present photoswitches.…”
Section: Discussionmentioning
confidence: 99%
“…Given the temperature-dependent change of the lifetime, we predicted that Mpphot perceives temperature using the lifetime of active LOV2 to selectively induce the accumulation response or the cold-avoidance response. To test this possibility, we used an amino acid substitution (V594T) (13) (Fig. S6) that accelerates the speed of thermal reversion fourfold and confirmed that the lifetime of active LOV2…”
Section: Significancementioning
confidence: 99%